Inovasi Pembelajaran Online di Era Pandemi Covid-19 Menggunakan Media Audio dan Video - A. Zaenal Arifin (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2020)
Online learning is being used due to the Covid-19 pandemic. This situation then causes changes in the learning patterns carried out. Teachers are required to innovate in carrying out teaching and learning activities so that students can still carry out learning amid the pandemic. The method used in this research is a qualitative approach with a descriptive design. The data in this study came from primary data and secondary data. Data collection used questionnaires and interviews conducted online to triangulate data. Learning using audio and video media has the advantage of being flexible, practical, creative, easily accessible anywhere and anytime, and can explain subject matter quite well in online learning. The implications of this research finding can be a support for online learning studies in the Covid-19 pandemic era on a broader scale in promoting good and innovative learning.